Inflammatory Microenvironment of Skin Wounds - Wang, Zhen; Qi, Fang; Luo, Han; Xu, Guangchao; Wang, Dali (Frontiers in Immunology, 2022)
Wound healing is a dynamic and highly regulated process that can be separated into three overlapping and interdependent phases: inflammation, proliferation, and remodelling. This review focuses on the inflammation stage, as it is the key stage of wound healing and plays a vital role in the local immune response and determines the progression of wound healing. Inflammatory cells, the main effector cells of the inflammatory response, have been widely studied, but little attention has been paid to the immunomodulatory effects of wound healing in non-inflammatory cells and the extracellular matrix. In this review, we attempt to deepen the concept of the wound-healing microenvironment in the inflammatory stage by focusing on the interactions between cells and the extracellular matrix, as well as their role in regulating the immune response during the inflammatory stage. We hope our findings will provide new ideas for promoting tissue regeneration through immune regulation.